Successful sphincter preservation and long-term survival in a patient with ultra-low locally advanced rectal cancer treated with photodynamic therapy combined with multimodal treatment: a case report and literature review - Dan Zou; Baohong Gu; Yifan Li; Ying Yan; Huanhuan Ma; Kai Wang; Weiyi Chen; Bofang Wang; Hao Chen (Therapeutic Advances in Medical Oncology)
Ultra-low locally advanced rectal cancer presents significant challenges for sphincter-preserving surgery due to its anatomical constraints and limited response to conventional neoadjuvant therapies. This case report describes a patient diagnosed with stage IIIb (cT3N2M0) ultra-low rectal cancer who had a strong preference for sphincter preservation. Given the suboptimal efficacy of standard treatments in achieving sufficient tumor downstaging, a comprehensive 6-month neoadjuvant regimen was implemented, combining photodynamic therapy (PDT), chemotherapy, targeted therapy, and immunotherapy. PDT selectively induced tumor necrosis, disrupted the tumor vasculature, enhanced therapeutic agent penetration, and transformed the tumor microenvironment into an immune-responsive state. This multimodal approach resulted in significant tumor regression, facilitating sphincter-preserving radical resection. Postoperative pathological examination confirmed a pathological complete response, and the patient remains disease-free, with a progression-free survival exceeding 48 months. This case highlights the potential of a multimodal treatment approach, combining PDT with systemic therapies, to enhance tumor downstaging, potentiate the efficacy of immunotherapy, and improve sphincter preservation rates in ultra-low locally advanced rectal cancer. This integrated strategy offers a promising approach for optimizing clinical outcomes in these challenging cases.